Inflation and welfare in an OLG economy with a privately provided public good - Gaetano Bloise; Sergio Currarini; Nicholas Kikidis (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we study the welfare effects of monetary policy in a simple overlapping generation economy in which agents voluntarily contribute to a public good. Inflation has two effects at equilibrium: it increases voluntary contributions and it misallocates private consumption across time. We show that the aggregate effect is welfare-improving for "not too large" inflation rates. Moreover, there exists an optimal inflation rate.
Keywords: H41; E52; D91; 330; Optimal inflation; public goods; voluntary contributions; Öffentliche Güter; Privatisierung; Inflation; Wohlfahrtsanalyse; Overlapping Generations; Theorie